Kualitas Spermatozoa Ayam Kampung dan Ayam Arab dengan Lama Simpan yang Berbeda pada Suhu Ruang - Enike Dwi Kusumawati; Aju Tjatur Nugroho Krisnaningsih; Aditya Umbu Kulli Walangara (Jurnal Sains Peternakan, 2020)
This research was conducted at the Laboratory of the Faculty of Animal Husbandry, University of Kanjuruhan Malang, which began in March until May 2019. The purpose of this study was to study the quality of semen of Kampung Ayam Arabian funds with long stored Arabs that produce in spaces. In this study, the material used was cement of Kampung chickens and Arabic chickens which were requested from two male chickens and 2 male Arab chickens needed 1.5-2 years that had a body weight of ± 2.5 kg and each tail was accommodated 1 time per day and in one shelter done 1 ejaculation. The laboratory test method uses a completely randomized design (factorial). The research treatment is storing time 0, 1, 2, 3, and 4 hours. Each payment is repeated ten times. The data obtained were analyzed using analysis of variance. The conclusion of this study is that there is an effect of shelf life on the quality of spermatozoa. After 4 hours motility is not feasible for IB, after 4 hours the viability is not feasible for all, after 4 hours the abnormality is not feasible for all.